Correlates of self-concept of Filipino intermediate school pupils - Floresca, Eufemia Rimando 1939- (1979)
This study sought to establish the relationship between intermediate pupils' self-concept (PSC), mothers'- fathers'-and teachers' percept of the children and other variables. The study consisted of 88 randomly selected intermediate school pupils at the Naguilian Elementary School, school year 1979-1980. The Pearson Product Moment Correlation Coefficient was used. The findings of the study showed that a highly significant relationship exists between PSC and mother's percept of their children. This was the highest correlation between the paired variables.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Self-perception in children